Between rhetoric and reality: the relevance of substantive equality approach to addressing gender inequality in Mozambique - Durojaye, Ebenezer (Afrika Focus, 2017)
The purpose of this article is to examine the socio-cultural challenges that continue to limit women’s enjoyment of their fundamental rights and freedoms in Mozambique. In this regard, this article focuses on three areas of gender inequality – denial of inheritance rights, sexual violence and early/ child marriage -in the country. In addition, the article, using a substantive equality approach, critically examines whether the steps and measures taken by the government of Mozambique to address gender inequality are consistent with its obligations under international human rights law. For the purpose of this analysis, the article focuses on Mozambique’s obligations under the Convention on the Elimination of All forms of Discrimination against Women (CEDAW) and the Protocol to the African Charter on the Rights of Women (African Women’s Protocol). The article concludes by making suggestions on how Mozambique can better safeguard the rights of women and improve their status. Key words : gender inequality, human rights, socio-cultural practices, Mozambique